Thermal manikins controlled by human thermoregulation models for energy efficiency and thermal comfort research – A review. (October 2017) - Psikuta, Agnes; Allegrini, Jonas; Koelblen, Barbara; Bogdan, Anna; Annaheim, Simon; Martínez, Natividad; Derome, Dominique; Carmeliet, Jan; Rossi, René M.
Abstract: As technology has advanced, the increasing pressure on energy usage reduction and expectations of consumers regarding comfort have made the requirements posed on clothing and control of the indoor climate more demanding. These goals, in turn, require advanced and reliable analytical methods that can faithfully relate to the human thermal behaviour and sensational perception. On the other hand, the concurrent development of simulation tools for human thermoregulation and thermal manikins has been progressing rapidly and continuously over the past two decades. Recent advances in computation technologies have facilitated computer simulation of sophisticated human thermo-physiological regulation mechanisms at high spatial and temporal resolution. Improvements in manufacturing techniques and control strategies have resulted in the development of highly sophisticated thermal manikins. These versatile evaluation instruments combine fine spatial resolution with high measurement reliability and system responsiveness. When coupled with a thermo-physiological model, a thermal manikin becomes an adaptive manikin that is capable of mimicking realistic dynamic human thermo-physiological responses to a given environment. There are already several such manikins in operation, mainly in the clothing research field but also in the built environment research. This review paper aims at discussing the opportunities and constraints of adaptive manikins, and more particularly, the manikin-based methodologies developed for the improvement of energy efficiency and determination of the human response in the fields of environmental engineering, car industry, and clothing research.